Baca al-Qur`an sebagai Sanksi Pelanggar Lalu Lintas: Integrasi Nilai Religius dan Penegakan Hukum di Lombok Tengah Perspektif Hifzh al-Din - Rahmad WD (Al Muhkam: Journal of Islamic Law and Jurisprudence, 2025)
Law enforcement in Indonesia continues to undergo dynamic development, one of which is reflected in the integration of religious values into the mechanisms of positive law. One notable innovation is the practice of Qur’an-reading traffic sanctions (tilang baca Al-Qur`an) in Lombok Tengah, where traffic offenders are sanctioned by being required to read verses of the Qur’an as a form of legal education and religious moral guidance. This study aims to analyze the integration of religious values particularly the concept of hifzh al-din within the framework of maqasid sharia, in this law enforcement practice. The research questions addressed are how the Qur’an-reading traffic sanction is implemented in Lombok tengah, and how the value of hifzh al-din is integrated into this mechanism, and what challenges, opportunities, and social impacts arise from its implementation. This study employs a qualitative approach, utilizing field research methods, in-depth interviews, and analysis of legal and religious documents. The findings indicate that the Qur’an-reading traffic sanction fosters legal awareness grounded in religious values while promoting a more humanistic and educative approach to law enforcement. This practice represents a contextual embodiment of maqasid sharia, particularly hifzh al-din, within local law enforcement. Despite facing legal-formal challenges and resistance from certain segments of society, the Qur’an-reading traffic sanction demonstrates potential as an alternative model of law enforcement that is contextual, spiritual, and rooted in local wisdom.